Spin wave behavior and controlled switching of a novel non-trivial magnetic texture in Co/Pt nanodiscs - Nimisha Arora; Yogesh Kumar; Pintu Das (APL Materials)
This work discusses the rich phase diagram of non-trivial, chiral magnetic textures/states in confined ultrathin nanodiscs of the ferromagnetic/heavy-metal bilayer. These magnetic textures are realized as a minimum-energy state during an external magnetic field sweep for a range of nanodisc’s diameter. Our micromagnetic simulation-based investigation reveals a robust non-trivial “X” state among several other previously reported textures, which can be stabilized for a wide range of diameters and external magnetic fields. The underlying energetics behind the stabilization of this novel texture are examined. Furthermore, we have investigated the nature of radial and breathing spin wave modes excited in these magnetic textures via a temporal magnetic field pulse applied out-of-plane of the sample. Our studies reveal non-reciprocal spin wave modes excited exclusively in the non-trivial “X” state. Furthermore, a transformation of the non-trivial “X” state into an extended skyrmion within a few nanoseconds is demonstrated by applying an external sinusoidal magnetic field at the frequency of its eigen spin wave mode. We also show a clear correlation between the behavior of excited spin wave modes and the underlying magnetic textures tuned by varying external magnetic fields.